ANATOMICAL VARIANTS OF THE PERSISTENT MEDIAN ARTERY AND INCOMPLETE SUPERFICIAL PALMAR ARCH: A CADAVERIC CASE SERIES (Asian Journal of Medical Research and Health Sciences, 2026)
The vascular anatomy of the human upper extremity exhibits significant morphological diversity, often driven by complex remodelling variations during embryonic development. This case series documents four distinct, high-risk neurovascular variations of the superficial palmar circulation identified during gross anatomical dissections, highlighting a critical complete loss of the hand's classic collateral safety net. While traditional anatomy dictates a complete superficial palmar arch formed by the radial and ulnar arteries, these specimens demonstrate how embryonic remodelling failures can drastically alter hand haemodynamics. The variations range from a persistent median artery (PMA) acting as a dominant, non-communicating central conduit for digital perfusion, to an isolated, incomplete superficial palmar arch that leaves a definitive hemodynamic gap between independent medial and lateral digital zones. Clinically, a patent, large-calibre palmar-type PMA traverses the carpal tunnel alongside the median nerve, acting as a space-occupying lesion that heavily predisposes individuals to compression syndromes. Most critically, because these architectural variants replace the standard interconnected palmar arcade with independent territorial perfusion, specific digits are left relying entirely on a single, isolated vessel for survival. Under these conditions, the surgical harvesting, traumatic laceration, or inadvertent ligation of any of these un-anastomosed trunk arteries eliminates all collateral pathways, risking sudden and catastrophic digital ischemia or tissue necrosis. This series emphasizes that a thorough understanding of upper limb vascular anomalies, paired with routine preoperative objective imaging such as colour Doppler ultrasonography, is paramount for hand surgeons, plastic reconstructive surgeons, and interventional radiologists to preserve vital digital perfusion and ensure safe surgical margins during operative procedures.